BRS SCS BELLUNA – a new banana cultivar for processing and fresh consumption - Ramon Felipe Scherer (Agropecuária Catarinense, 2020)
The new banana cultivar, BRS SCS Belluna (AAA), was developed by the Embrapa and Epagri banana breeding programs for processing and fresh consumption. It is noteworthy differentiated nutritional qualities, since its fruits are rich in fiber and have lower carbohydrate and caloric content when compared to fruits of the most traded subgroups in the country, Prata and Cavendish. ‘BRS SCS Belluna’ is also resistant to Panama disease and to Sigatoka disease complex, major plant health problems in Brazil. The cultivar has yield potential up to 40t ha-1 under favorable environmental conditions. Thus, it is recommended to plant the 'BRS SCS Belluna' in the country, highlighting the state of Santa Catarina, where the studies were conducted.